The role of the legislative branch in establishing and coordinating the functioning of other branches of government - Turchynov, Kyrylo (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
This article explores the functions of the legislative branch and their impact on the formation and organization of other branches of government in political life. The legislative branch plays a crucial role in establishing legal norms that regulate the functioning of other branches of government and state bodies. The article analyzes functions such as legislative, constituent, and parliamentary control, which form the basis of state governance in the country.The article highlights that the parliament serves as the legislative body responsible for enacting laws and regulating their amendments. It also examines the constituent function of the parliament, which determines the legal basis for the creation of other state bodies. The role of parliamentary control in ensuring compliance with the law and oversight of the activities of other branches of government is also explored.The authors discuss that the effective functioning of the legislative branch is key to the stability and development of the state. They analyze the role of parliament in the process of law formation, establishment of state institutions, and ensuring control over their activities. It is noted that parliamentary activity is of great importance for maintaining democratic principles and the rule of law.